Analysis Of The Application Of Play Therapy: Puzzles To Overcome Anxiety Due To Hospitalization In Children At Hospital: Analisis Penerapan Terapi Bermain: Puzzle Untuk Mengatasi Kecemasan Akibat Hospitalisasi Pada Anak Di Rumah Sakit - Miradwiyana, Bara; Putri, Clarisa Setyo (Essential English Grammar, 2024)
Hospitalization stress is a condition such as anxiety, sadness and fear that children and their families experience while undergoing treatment in hospital. The short-term impact that can occur due to anxiety and fear that is not treated immediately is rejection of treatment and care, which can result in an increase in days of care, and cause the child's condition to get worse. The aim of this research is to reduce anxiety due to hospitalization in children using puzzle play therapy. This research method uses a case study method carried out on children aged 4 and 6 years for 3 days with a duration of 15 minutes per meeting. The puzzle that will be given to children aged 4 years is 9 pieces, while children aged 6 years are given 12 pieces. The puzzles given to the two children were in the form of cute pictures. Before and after administering puzzle playing therapy, characteristics and anxiety scales were assessed using the Face Image Scale assessment. The results of the intervention that had been carried out for 3 days showed a decrease in the anxiety scale in the case of the 1st child who experienced a decrease in anxiety from a scale of 4 to 3. Meanwhile in the case of the 2nd child there was a decrease from an anxiety scale of 3 to 2. The conclusion is that there is effectiveness of puzzle playing therapy for reduce anxiety due to hospitalization in children. It is hoped that this puzzle play therapy can be applied in hospitals, especially in children's rooms, to minimize anxiety in children during hospitalization.